Effects of hydrogen flowrate on carbon nanotube production at low temperature via floating catalyst chemical vapor deposition method - Zadeh, Elmira Habashi (2014)
Well-aligned multiwall carbon nanotubes (CNTs) were successfully synthesized by floating catalyst chemical vapour deposition method at 600 0c. In this research, benzene and ferrocene were used as carbon source and catalyst respectively. Hydrogen flow rate and preheating temperature were considered as variables in this research in order to study the impacts of these parameters on the quantity, structure and morphology of produced CNTs. The effect of hydrogen flow rate on the temperature variation inside the reactor was studied as well. The parameters such as reaction time (45 min), synthesis temperature (600 0c) and amount of ferrocece (200ml) were kept constant during the experiments. Argon was used at flow rate of 350 ml/min before and after the reaction for creating an inert atmosphere and preventing oxidation accordingly. The hydrogen flow rate was varied from 150 ml/min to 450 ml/min with increment of 50 ml/min. The preheating temperature was set at 200 and 300 0c. The morphology and structure of the produced CNTs were analysed by Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM), X ray Diffraction analysis (XRD). The purity of the product were determined by using Thermal Gravimetric Analyser (TGA). The results show that the quantity of CNTs has been increased with the increase of hydrogen flow rate and preheating temperature. The quality of CNTs has been improved by increasing the hydrogen flow rate from 150 ml/min to 350 ml/min. The study reveals that lower pre-heating temperature (200 0c) has led to better quality. It was found that well-aligned CNTs were produced with different purity, depending on the hydrogen flow rated at 200 0c preheating temperature. The results indicate that the quality and quantity of CNTs are affected by both hydrogen flow rate and preheating temperature. The temperature variation inside the reactor in different hydrogen flow rate is negligible.